2000
DOI: 10.1021/jf000830w
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Steryl, Stanyl, and Steroid Esters by Esterification and Transesterification in Vacuo Using Candida rugosa Lipase as Catalyst

Abstract: Sterols (sitosterol, cholesterol, stigmasterol, ergosterol, and 7-dehydrocholesterol) and sitostanol have been converted in high to near-quantitative yields to the corresponding long-chain acyl esters via esterification with fatty acids or transesterification with methyl esters of fatty acids or triacylglycerols using lipase from Candida rugosa as biocatalyst in vacuo (20-40 mbar) at 40 degrees C. Neither organic solvent nor water is added in these reactions. Under similar conditions, cholesterol has been conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 12 publications
(11 reference statements)
3
47
2
Order By: Relevance
“…Osanai (3) reported the synthesis of an oleic acid ester of cholesterol using lipase and organic hydrocarbon solvents such as cyclohexane, benzene, and toluene, whereas Shimada et al (4) reported the synthesis of a DHA ester of cholesterol in a two-phase medium containing 30% water. Furthermore, Weber et al (5)(6)(7) efficiently synthesized steryl esters by carrying out the enzymatic reaction under reduced pressure to remove the water and alcohol from the reaction system.…”
mentioning
confidence: 99%
“…Osanai (3) reported the synthesis of an oleic acid ester of cholesterol using lipase and organic hydrocarbon solvents such as cyclohexane, benzene, and toluene, whereas Shimada et al (4) reported the synthesis of a DHA ester of cholesterol in a two-phase medium containing 30% water. Furthermore, Weber et al (5)(6)(7) efficiently synthesized steryl esters by carrying out the enzymatic reaction under reduced pressure to remove the water and alcohol from the reaction system.…”
mentioning
confidence: 99%
“…Among various catalysts, pyridine, PB, TEA, NBS and DMAP are effective catalysts and widely used in various reactions. Lipase also has been used in organic media for the catalysis of esterification and transesterification reactions (Weber et al 2001;Yadav and Devi 2004). As shown in Table 1, MAXH with a DS rang of 0.35-0.94 were achieved at the catalysts concentration of 20 wt% (based on the dried xylan-rich hemicelluloses weight).…”
Section: Effect Of the Chemical Reaction Conditions On The Ds Of Maxhmentioning
confidence: 99%
“…2.8 Purity analysis and structure characterization 2.8.1 Thin layer chromatography (TLC) analysis [22] Products were diluted in the chloroform and spotted, compared with phytosterols and PUFA. Development was carried out in a petroleum ether (60-908C)/ether/acetic acid 90:10:1 v/v/v and the spots were visualized by iodine vapor and exposure in oven set at 1808C for 5 min.…”
Section: Solubility Of Sterol Ester Of Pufa In Vegetable Oilmentioning
confidence: 99%